2020
DOI: 10.3390/agronomy10081116
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Selection by Jointly Optimizing Biomass Productivity, Biological Nitrogen Fixation, and Transpiration Efficiency: Application to Two Crotalaria Species

Abstract: Crotalaria spectabilis and Crotalaria juncea are cover crops (CC) that are used in many different regions. Among the main attributes of these species are their high potential for biomass production and biological fixation of nitrogen (BNF). Attempting to maximize these attributes, while minimizing water consumption through high transpiration efficiency (TE), is a challenge in the design of sustainable agricultural rotations. In this study, the relationship between biomass productivity, BNF, and TE in C. specta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(65 reference statements)
0
4
0
1
Order By: Relevance
“…In this context, use of legumes as cover crops in agricultural rotations may reduce the production costs associated with the use of mineral N fertilizers, and also result in environmental benefits. In order to optimize biomass productivity, biological nitrogen fixation, and transpiration efficiency, Berriel et al [36] evaluated the application of two Crotalaria species, specifically C. juncea and C. spectabilis grown under extreme environmental conditions with the finality to maximize their beneficial attributes, while minimizing water consumption through high transpiration. Their results showed that the C. spectabilis has advantages as legumes cover crop over C. juncea, in terms of transpiration as indicated by a 13 C isotopic analyses.…”
Section: System Innovations Based On Organic Fertilization and Waste ...mentioning
confidence: 99%
“…In this context, use of legumes as cover crops in agricultural rotations may reduce the production costs associated with the use of mineral N fertilizers, and also result in environmental benefits. In order to optimize biomass productivity, biological nitrogen fixation, and transpiration efficiency, Berriel et al [36] evaluated the application of two Crotalaria species, specifically C. juncea and C. spectabilis grown under extreme environmental conditions with the finality to maximize their beneficial attributes, while minimizing water consumption through high transpiration. Their results showed that the C. spectabilis has advantages as legumes cover crop over C. juncea, in terms of transpiration as indicated by a 13 C isotopic analyses.…”
Section: System Innovations Based On Organic Fertilization and Waste ...mentioning
confidence: 99%
“…Plants of the Crotalaria genus are widely used as cover crops or in partnership with other cultures having a large biomass capacity and biological nitrogen fixation (by the symbiosis that they perform with bacteria of the Rhizobium genus) (Berriel, Monza, & Perdomo, 2020). Furthermore, they attract a great diversity of insects and natural enemies (Supriyadi, Wijayanti, Arniputri, Puspitarini, & Dwiyatno, 2019;Tavares et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Д а л ь н е й ш и е п е р с п е к т и в ы и с с л е д о в а н и я к у л ь т у р ы. В современном мире растет потребность в производстве волокна и развитии технологии органического земледелия. Поскольку кроталярия может выращиваться в больших коммерческих масштабах как покровная и лубяная культура (118), во многих странах мира идет процесс ее постепенной интродукции в диверсифицированные севообороты в качестве сидеральной культуры для улучшения здоровья почвенных экосистем и уменьшения численности галловых нематод. Эффективным агротехническим приемом, повышающим адаптацию культуры к условиям определенной почвенно-климатической зоны, может служить использование биопрепаратов на основе консорциума полезных микроорганизмов -клубеньковых и ассоциативных ризобактерий, а также грибов арбускулярной микоризы.…”
Section: рис 2 географическое распространение культуры Crotalaria Jun...unclassified